AIDS-related malignant disease. (May 2022) - Pria, Alessia Dalla; Bower, Mark
Abstract: Immunodeficiency, whether congenital or acquired, iatrogenic (e.g. allograft recipients) or infectious (e.g. human immunodeficiency virus (HIV)), is associated with an increased risk of malignancy. In the case of HIV-related immunodeficiency, most cancers are associated with oncogenic virus co-infection. Although the overall risk of any cancer is increased 2–3-fold in people living with HIV, there are three acquired immune deficiency syndrome (AIDS)-defining cancers whose relative risk is dramatically higher: Kaposi sarcoma, high-grade B cell non-Hodgkin lymphoma (including primary cerebral lymphoma) and invasive cervical cancer. Since the introduction of combination antiretroviral therapy, the incidence of the AIDS-defining malignancies has declined. In contrast, the effect on the incidence of other cancers has been small; however, the increased longevity of people living with HIV and the ageing of this population mean that there has been a rise in number of cases of non-AIDS-defining malignancies. Recent advances in the management of malignancy in people with HIV have led to outcomes similar to those of the general population.